Cancer mortality and morbidity in employees of the United Kingdom Atomic Energy Authority, 1946-86. - Fraser, P. (Nature Publishing Group, 1993)
In further analyses of a cohort of 39,718 United Kingdom Atomic Energy Authority employees after 7 more years follow-up, cancer mortality, based on 1,506 deaths in 1946-86, was 20% below the national average. Prostatic cancer mortality showed a statistically significant association with external radiation exposure, largely confined to men who were also monitored for internal contamination by radionuclides other than plutonium. Prostatic cancer mortality was highest in radiation workers at Winfrith. In women monitored for radiation exposure, mortality from cancer of the uterus (including the cervix uteri) was increased relative to other employees, and, showed a statistically significant association with external radiation exposure. While there were some other statistically significant results, as would be expected by chance alone when multiple comparisons are made, there were no other cancer sites with consistently exceptional findings. Point estimates for risk associated with increasing exposure to radiation suggest a decrease of four deaths per 10(4) person-years per Sv for leukaemia and an increase of 20 deaths for all cancers except leukaemia, but confidence intervals indicate that a wide range of values are compatible with the data. Cancer morbidity based on 1,699 registrations in 1971-84 was 12% below the national average. Findings from site-specific analyses largely replicated those of the mortality analyses.